How do Tourists Perceive Risk and Develop Travel Preparedness? Influence of Destination Attributes and Knowledge - Rahmafitria, Fitri; Setiyorini, Heri Puspito Diyah; Hindayani, Purna; Oktadiana, Hera; Ramadhan, Andrian (Jurnal Manajemen Hutan Tropika, 2025)
This study explores how destination attributes, such as accessibility, natural attractions, facilities, and disaster knowledge, influence tourists' risk perceptions, ultimately shaping their travel preparedness. Data were collected through questionnaires distributed to 806 tourists visiting a tsunami-prone beach destination in Indonesia. Partial Least Squares Structural Equation Modeling (PLS-SEM) was implemented in the analysis. The findings indicate that accessibility and well-developed tourist facilities tend to lower tourists’ perceived risk, while disaster knowledge heightens it, leading to improved preparedness. Tourists generally feel safer when destinations offer accessible amenities and infrastructure, yet this sense of security may inadvertently decrease their readiness for disasters. This situation creates a paradox: While enhanced accessibility and high-quality amenities contribute to visitor satisfaction, they can unintentionally lower risk perception and preparedness levels. The study challenges the conventional view that accessibility and amenities are inherently beneficial, highlighting the importance of balancing these attributes with proactive risk management strategies. Destination providers, destination management organizations (DMOs), and governments should enhance tourists’ disaster awareness through well-crafted guidelines, educational campaigns, and community engagement programs; these efforts help equip tourists with the necessary knowledge to respond effectively in emergency situations. At the same time, they contribute to the development of safer and more enjoyable tourist destinations.